DIAMONDOIDS AND BASIN MODELLING REVEAL ONE OF THE WORLD'S DEEPEST PETROLEUM SYSTEMS, SOUTH CASPIAN BASIN, AZERBAIJAN. (17th March 2020) - Goodwin, N. R. J.; Abdullayev, N.; Javadova, A.; Volk, H.; Riley, G.
Abstract : The South Caspian Basin has been one of the world's most prolific petroleum provinces since the 19th Century. However, despite the large number of discovered petroleum accumulations, the source rock sequence has not been penetrated by the drill in the offshore basin and is therefore poorly defined. In this paper, geochemistry together with broad estimates of in‐place volumes of petroleum fluids, onshore outcrop data and basin modelling have been used to place constraints on the source rock description. Diamondoids, the most thermally stable group of hydrocarbons, have been measured in a suite of liquid petroleum samples from Pliocene fluvio‐deltaic sandstone reservoirs at the Shah Deniz gas‐condensate field and the Azeri‐Chirag‐Gunashli oil field, offshore Azerbaijan. Samples from both fields exhibit elevated concentrations of diamondoids and C29 steranes, indicating a mixture of thermally cracked and non‐cracked petroleum. We use diamondoid concentrations to estimate that 4.8 B brl of oil may have been cracked to 12 Tcf of gas below the Shah Deniz reservoirs. Source rock properties from the outcropping Oligocene – Miocene Maikop and Diatom Formations have been used to model source rock maturation. The results indicate that pre‐cracking volumes of petroleum could be explained reasonably by the presence of source rock intervals in the offshore that are of similar richness but increased thickness compared to measured onshore outcrops. Relatively high diamondoid concentrations in Shah Deniz condensate (up to 160 ppm 3‐ + 4‐methyldiamantanes) are in agreement with gas isotope compositions (δ 13 C1 – δ 13 C3 ) with respect to thermal maturity. Both parameters indicate the presence of source rock that is at a high level of thermal maturity at a vitrinite reflectance equivalent (VRE) of ca. 1.5–2.0% Ro . Given the low geothermal gradients in the South Caspian Basin (16 – 17°C/km at Shah Deniz) and the relatively high temperatures required for maturation due to rapid, relatively recent burial and heating, the source rock must be buried to depths in excess of 13 km in the Shah Deniz drainage area. In the absence of any evidence of a working Mesozoic petroleum system in the South Caspian Basin, this depth of burial highlights the significant thickness of Paleogene sediments in the offshore basin. Of prolific petroleum‐producing basins, only in the deep‐water Gulf of Mexico are actively‐generating source rocks buried to similar depths.